THE FINANCIAL FAILURE OF FIRST NATIONS EDUCATION IN CANADA: The Challenges for Indigenous Religious Freedom in Canada Today (Canadian Journal of Native Studies, 2026)
AbstractThe underfunding of First Nations K-12 education in Canada has createda disparity in the quality of education received by First Nationsstudents compared to non-First Nations students. Understanding theconnection between funding and student outcomes might prove usefulin confronting this disparity. Additional funding will not resolve all educationproblems, so those evaluating funding and policy interventionswould benefit from considering factors such as efficiency, effectiveness,equity and the social context of learning.To create social change and understand if policy is a suitable tool for intervention,it is helpful to understand why the gap in education exists. Ifthe gap does result in disparity of education outcomes, it is a worthwhilesubject to explore. In this case, the gap is suggested to affect student outcomesand Indigenous communities and organizations have reiteratedthis to the federal government (Assembly of First Nations, 2017).